Microwave assisted extraction of inositols for the valorization of legume by-products. (November 2020) - Zuluaga, Ana M.; Mena-García, Adal; Soria Monzón, Ana C.; Rada-Mendoza, Maite; Chito, Diana M.; Ruiz-Matute, Ana I.; Sanz, Maria L.
Abstract: Currently there is great interest in exploitation of agrofood by-products, such as those from legumes, as source of bioactive ingredients. To that aim, characterization of cyclitol and sugar composition of pods and seeds from different legume species has been carried out. A green Microwave Assisted Extraction (MAE) method was optimized for extraction of bioactive inositols, and both pod and seed yields were compared with those obtained by conventional reflux extraction. A subsequent Saccharomyces cerevisiae treatment was also evaluated for removal of interfering coextracted sugars. myo -Inositol was present in all legume pods and seeds and galactinol in most seeds. c hiro -Inositol was found in soybean and basul, whereas outstanding pinitol concentrations were only detected in soybean. The optimized MAE method provided extracts rich in pinitol from soybean pods (41.5–58.0 mg g −1 ) and seeds (5.3–7.5 mg g −1 ). Removal of 97% of interfering sugars in MAE soybean pod extracts was achieved by yeast treatment. Highlights: Cyclitol and sugar composition of legume seed and pods was determined. Soybean pods could be considered a promising source of pinitol. Microwave assisted extraction was optimized to obtain bioactive inositol extracts. A subsequent yeast treatment was used to remove interfering sugars from extracts. This methodology allows revalorization of legume byproducts.